ChemInform Abstract: Silver Triflate‐Catalyzed Cyclization of 2‐Amino‐6‐propargylamineazines Leading to Iminoimidazoazines. Issue 39 (23rd September 2014) - Chioua, Mourad; Samadi, Abdelouahid; Soriano, Elena; Infantes, Lourdes; Marco‐Contelles, Jose
Abstract The scope, limitations, and mechanism of the title cyclization reaction are described.